Preparation method and application of gel mixed matrix membrane based on in-situ MOF
By combining the in-situ growth MOF gel with Pebax-1657 particles, a hybrid matrix membrane with high interfacial compatibility and separation performance was prepared, which solved the problem of degradation of separation performance of traditional membranes under high loads and achieved CO2/N2 Efficient separation of gases reduces greenhouse gas emissions.
Patent Information
- Application Number
- CN202411251780.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-09-09
AI Technical Summary
Traditional gas separation membranes are difficult to maintain good interfacial compatibility and separation performance under high loads, resulting in a degradation of separation performance. The existing MOF gel membranes also have agglomeration problems under high loads, affecting the separation performance.
A method of preparing an in-situ MOF gel mixed matrix membrane is adopted to form a MOF gel by reacting zinc nitrate hexahydrate, dimethylimidazole and triethylamine in an ethanol-water mixed solvent to form a MOF gel and bind to Pebax-1657 particles. , the mixed matrix membrane is obtained by dialysis and drying, enhancing the interfacial compatibility of the filler and polymer and gas separation performance.
It achieves good interface compatibility between MOF and polymer under high load, improves gas separation performance, especially selectivity and permeability in CO2/N2 gas separation, and effectively reduces greenhouse gas emissions.
Smart Images

Figure CN119281124A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of gas separation membrane materials, and in particular to a preparation method and application of an in-situ MOF gel mixed matrix membrane Background Art
[0002] With the rapid development of the industrial economy, the concentration of carbon dioxide (CO2) in the atmosphere has increased year by year. According to a report in 2017, the concentration of CO2 in the atmosphere reached the highest level in 800,000 years, 405ppm (parts per million), which became one of the hottest years that year, attracting widespread attention worldwide. As one of the main greenhouse gases, the large-scale emission of CO2 is the main cause of the adverse consequences such as sea level rise, global warming and climate anomalies. At the same time, CO2 has great application value in food processing, industrial production, oil extraction and other fields. Therefore, the efficient separation of CO2 from emission sources (coal-fired power plants, flue gas from steel mills, etc.) has extremely important scientific significance and great engineering application value. Compared with other separation technologies, membrane separation technology has the advantages of low investment and low energy consumption, and has been valued and industrially applied in recent years. However, it is difficult for traditional gas separation membranes to break through the trade-off effect of permeability and selectivity to achieve good separation performance. Therefore, the mixed matrix membrane (MMM) that combines the advantages of organic membranes and inorganic membranes has the characteristics of high selectivity, thermomechanical stability and plasticization resistance. It is the best choice to break through the upper limit of separation performance and soon became a research hotspot for high-performance gas separation membranes.
[0003] As an important component of mixed matrix membranes, the selection of fillers is crucial. Although traditional inorganic fillers can improve gas separation performance, they will form non-selective voids when the loading is too large, resulting in a decrease in separation performance. Although mixed matrix membranes based on MOFs materials have more advantages than traditional inorganic fillers MMM, they will agglomerate under high loads and affect separation performance.
[0004] The crystallization of MOF mainly includes two processes: nucleation and crystal growth. When the aggregation rate of nanoparticles exceeds the rate of crystal growth, MOF gel will be produced. MOF gel shows a randomly cross-linked gel network structure with high permeability. At present, there are a large number of reports on the preparation of MMMs by mixing MOFs fillers with polymers and a small number of reports on MOF gel MMMs, but MOFs-based MMMs with high loading and good interfacial compatibility and high separation performance need further research. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present invention is to increase the interfacial compatibility between MOFs and polymers and improve the gas separation performance of MMMs, thereby providing an in-situ MOF gel-based mixed matrix membrane and a preparation method thereof.
[0006] The technical solution of the present invention is: an in-situ MOF gel mixed matrix membrane and a preparation method thereof, comprising the following steps:
[0007] Step 1: Weigh a certain amount of dried Pebax-1657 particles, add ethanol-water mixed solvent, and heat under reflux at 90° C. to obtain solution A;
[0008] Step 2: Prepare materials for synthesizing MOF gel: zinc nitrate hexahydrate, dimethylimidazole and triethylamine. Dissolve zinc nitrate hexahydrate in an ethanol-water mixed solvent to obtain solution B, dissolve dimethylimidazole in an ethanol-water mixed solvent, and add a certain amount of triethylamine to the mixed solution to obtain solution C;
[0009] Step 3: Add solution B and solution C to solution A successively, stir and react to obtain a mixed solution;
[0010] Step 4: The mixed solution is transferred to a dialysis bag for dialysis, and the dialyzed mixed solution is transferred to a polytetrafluoroethylene culture dish. The culture dish is placed in an oven and a vacuum oven for drying to obtain a mixed matrix membrane.
[0011] As a preferred embodiment, in step 1, the mass fraction of solution A is 3.0 wt.%; and the mass ratio of ethanol to water in the ethanol-water solvent is 9 / 1.
[0012] As a preferred embodiment, in step 2, the mass volume ratio of zinc nitrate hexahydrate to ethanol water solvent in solution B is 0.024-0.072 g / ml; the mass volume ratio of dimethylimidazole to ethanol water solvent in solution C is 0.0264-0.0792 g / ml, and the mass volume ratio of dimethylimidazole to triethylamine is 2.64-3.57 g / ml; and the mass ratio of ethanol to water in the ethanol-water mixed solvent is 9 / 1.
[0013] As a preferred embodiment, in step 3, the molar ratio of zinc nitrate hexahydrate in solution B to dimethylimidazole in solution C is 1 / 2; the mass ratio of zinc nitrate hexahydrate in solution B to Pebax-1657 in solution A is 0.15-0.45; and the mass ratio of ethanol to water in the ethanol-water mixed solvent is 9 / 1.
[0014] As a preferred solution, in step 3, solution B is first added to solution A, stirred for 5 minutes, and then solution C is added after mixing, and the mixture is stirred and reacted for 60 minutes.
[0015] As a preferred embodiment, in step 4, the dialysate is a 90 wt. % ethanol-water mixed solution, and the dialysate is performed 4 times, each time for 12 hours.
[0016] As a preferred solution, in step 4, the film baking temperature in the oven is 40° C., and the film baking time is 24 h; the film baking temperature in the vacuum oven is 60° C., and the film baking time is 24 h.
[0017] The present invention also discloses an application of an in-situ MOF gel mixed matrix membrane in the selective separation of CO2 / N2 gases.
[0018] Compared with the prior art, the present invention has the following technical effects:
[0019] (1) The present invention utilizes a one-pot method to in situ grow MOF gel and increase the interfacial compatibility between filler and polymer, thereby preparing high-load MMMs with excellent performance.
[0020] (2) The present invention utilizes the network structure of the MOF gel itself to construct through-channels, thereby enhancing the gas separation performance.
[0021] Therefore, the in-situ MOF gel-based mixed matrix membrane of the present invention can be used to separate CO2 in mixed gases to achieve the purpose of reducing the greenhouse effect and alleviating ecological pressure. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The figure is a flow chart of the preparation of the mixed matrix membrane of the present invention.
[0023] Figure 2 Schematic diagram of mixed matrix membrane separation prepared by the present invention. DETAILED DESCRIPTION
[0024] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and implementation examples. In the present invention, unless otherwise specified, the raw materials required for preparation are all commercially available products well known to those skilled in the art.
[0025] See also Figure 1 In the preparation method of the mixed matrix membrane of the present invention, a zinc salt solution and a mixed solution of dimethylimidazole and triethylamine are successively added to a Pebax solution and stirred to perform an in-situ growth reaction; the reaction solution is placed in a dialysis bag for dialysis; after the dialysis is completed, the dialyzed solution is transferred to a polytetrafluoroethylene culture dish, and the mixed solution is dried to form a membrane.
[0026] See also Figure 2 A network of MOF gel-penetrating channels is formed in the mixed matrix membrane prepared by the present invention, thereby improving the gas permeation selectivity.
[0027] Example Preparation of mixed matrix membrane:
[0028] (1) Preparation of Pebax solution: First, weigh 3.0 g of dried Pbeax-1657 particles and transfer them to a three-necked flask. Add 100 g of a 90 wt.% ethanol-water mixed solvent to the three-necked flask. Insert a condenser into the three-necked flask. Place the three-necked flask in an oil bath and heat and stir at 90°C for 60 min to obtain a 3.0 wt.% Pebax solution.
[0029] (2) Preparation of reactant solutions: 0.12 g, 0.24 g, and 0.36 g of zinc nitrate hexahydrate were weighed and placed in experimental bottles numbered 1, 2, and 3, and 5 ml of a 90 wt.% ethanol-water mixed solvent was added to each of the bottles to prepare zinc nitrate solutions; 0.132 g, 0.264 g, and 0.396 g of dimethylimidazole were weighed and placed in experimental bottles numbered A, B, and C, and 5 ml of a 90 wt.% ethanol-water mixed solvent was added to each of the bottles to prepare dimethylimidazole solutions, and 50 μl, 80 μl, and 110 μl of triethylamine were added to A, B, and C, respectively, and mixed.
[0030] (3) Synthesis of ZIF-8 gel: Weigh three portions of 15 g of Pebax solution into reaction bottles numbered I, II, and III. Place the three reaction bottles on a stirring table and start stirring at a speed of 600 rpm. Add the solutions in experimental bottles No. 1, 2, and 3 to reaction bottles No. I, II, and III, respectively. After mixing, add the solutions in experimental bottles No. A, B, and C, respectively, and stir to react for 60 min.
[0031] (4) Preparation of mixed matrix membrane: The reaction solutions in reaction bottles I, II and III were transferred to dialysis bags and dialysis was started. The dialysate was a 90 wt.% ethanol-water mixed solution. The dialysis time was 12 h and the number of dialysis was 4 times. After the dialysis was completed, 8 ml of the dialyzed solution and the original Pebax solution were transferred to polytetrafluoroethylene culture dishes respectively and dried in a 40°C oven for 24 h. The culture dishes were then transferred to a 60°C vacuum oven and dried for 24 h to finally obtain the desired mixed matrix membrane.
[0032] Comparative Example Preparation of Mixed Matrix Membrane by Direct Blending Method:
[0033] (1) Preparation of ZIF-8 gel particles: Weigh 0.96 g zinc nitrate hexahydrate and 1.056 g dimethylimidazole and dissolve them in 20 ml of a 90 wt.% ethanol-water mixed solvent to obtain a solution of the two; add 320 μl of triethylamine to the dimethylimidazole solution and mix well to obtain a mixed solution; add the zinc nitrate hexahydrate solution to 60 g of a 90 wt.% ethanol-water mixed solution and stir for 5 min at a stirring speed of 600 rpm; add the dimethylimidazole-triethylamine mixed solution to the zinc nitrate hexahydrate solution and stir for 60 min; divide the solution after the reaction evenly into centrifuge tubes and centrifuge them twice at a centrifugal speed of 10,000 rpm for 90 min / time; first transfer the centrifuged product to an oven and dry it at 120°C for 12 h, then transfer it to a vacuum oven and dry it at 120°C for 12 h to obtain ZIF-8 gel particles.
[0034] (2) Preparation of mixed matrix membrane: 10 g of the Pebax solution in the example was weighed in a small glass bottle, and 0.045 g of ZIF-8 gel particles was added thereto. The mixture was stirred with a magnetic stirrer for 60 min at a stirring speed of 600 rpm to obtain a mixed solution. The mixed solution was transferred to a polytetrafluoroethylene culture dish and dried in an oven at 40°C for 24 h. The culture dish was then transferred to a vacuum oven at 60°C and dried for 24 h to finally obtain the desired mixed matrix membrane.
[0035] The permeability coefficient and selectivity test process of the gas in the following examples and comparative examples are as follows: The prepared mixed matrix membrane is tested under the operating conditions of 35°C and 2 bar. Its permeability performance is obtained by the Tima-lag method (constant volume-variable pressure method). The upstream gas enters the upper part of the membrane pool through the manual valve and pressure gauge control and is adjusted to the required pressure. When the test is started, the manual valve on the upper side of the membrane pool is opened, and the gas penetrates to the bottom through the MMMs in the membrane pool, and the pressure gauge below shows the pressure change on the downstream side of the membrane pool. Before the test, use a vacuum pump to evacuate all other gases in the pipeline and the permeation pool.
[0036] The permeability coefficient and selectivity of the gas in the membrane are calculated as follows:
[0037]
[0038]
[0039] Where i and j represent different gases. i , P j is the permeability coefficient of gas i, j in the membrane, the unit is Barrer (1Barrer = 1×10 -10 cm 3 (STP)cm / (cm 2·s·cmHg); L is the thickness of the film, in cm; V d is the volume of the downstream side, in cm 3 ; A is the effective membrane area, unit: cm 2 ; R is the universal gas constant, unit: Pa·m 3 ·mol -1 ·K -1 ; T is the permeation chamber temperature, unit K; P0 is the upstream pressure, unit cmHg; is the fitting line coefficient of the curve obtained by the time-lag method for gas i, in Pa / s; α i / j Select the separation factor for the gases gas i and gas j.
[0040] The gas separation performance of the MMMs prepared in the examples and comparative examples was tested at 35°C and 2 bar. The test results are shown in Table 1
[0041] Table 1
[0042]
[0043] Results: As can be seen from Table 1, for the mixed matrix membrane of the embodiment, as the mass fraction of gel ZIF-8 in the membrane increases from 0 to 45wt.%, the permeability coefficients of CO2 and N2 gradually increase, the selectivity of CO2 / N2 remains basically unchanged, and the performance of MMMs gradually improves. However, for the mixed matrix membrane prepared in the comparative example, the selectivity of the membrane decreases significantly when the content of gel ZIF-8 is the same. It can be seen that the mixed matrix membrane prepared based on in situ gel MOF can effectively improve the interfacial compatibility between gel MOF and polymer matrix and improve the separation performance of MMMs.
[0044] The above-described embodiments are preferred examples of the present invention, but do not limit the applicable scope of the present invention. Appropriate improvements can be made without departing from the principle of the present invention, and these improvements should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing an in-situ MOF gel mixed matrix membrane, characterized in that: The following steps are involved: (1) Weighing a certain amount of dried Pebax-1657 particles, adding an ethanol-water mixed solvent, and heating under reflux at 90° C. to obtain solution A; (2) Prepare materials for synthesizing gel MOF: zinc nitrate hexahydrate, dimethylimidazole and triethylamine. Dissolve zinc nitrate hexahydrate in an ethanol-water mixed solvent to obtain solution B, dissolve dimethylimidazole in an ethanol-water mixed solvent, and add a certain amount of triethylamine to the mixed solution to obtain solution C; (3) adding solution B and solution C to solution A successively, stirring for reaction, and obtaining a mixed solution; (4) The mixed solution is transferred to a dialysis bag for dialysis, and the dialyzed mixed solution is transferred to a polytetrafluoroethylene culture dish. The culture dish is placed in an oven and a vacuum oven for drying to obtain a mixed matrix membrane.
2. The method according to claim 1, characterized in that In step (1), the mass fraction of solution A is 3.0wt.%; and the mass ratio of ethanol to water in the ethanol-water solvent is 9 / 1.
3. The method according to claim 1, characterized in that In step (2), the mass volume ratio of zinc nitrate hexahydrate to ethanol water solvent in solution B is 0.024-0.072 g / ml; the mass volume ratio of dimethylimidazole to ethanol water solvent in solution C is 0.0264-0.0792 g / ml, and the mass volume ratio of dimethylimidazole to triethylamine is 2.64-3.57 g / ml; and the mass ratio of ethanol to water in the ethanol water solvent is 9 / 1.
4. The method according to claim 1, characterized in that: In step (3), the molar ratio of zinc nitrate hexahydrate in solution B to dimethylimidazole in solution C is 1 / 2; the mass ratio of zinc nitrate hexahydrate in solution B to Pebax-1657 in solution A is 0.15-0.45; and the mass ratio of ethanol to water in the ethanol-water mixed solvent is 9 / 1.
5. The method according to claim 1, characterized in that In step (3), solution B is first added to solution A, stirred for 5 min, and then solution C is added after mixing. The mixture is stirred and reacted for 60 min.
6. The method according to claim 1, characterized in that In step (4), the dialysate is selected from 90 wt.% ethanol aqueous solution, and the dialysate is performed 4 times, each time for 12 hours.
7. The method according to claim 1, characterized in that In step (4), the film-baking temperature in the oven is 40° C. and the film-baking time is 24 h; the film-baking temperature in the vacuum oven is 60° C. and the film-baking time is 24 h.
8. An in-situ MOF gel-based mixed matrix membrane prepared according to the method of any one of claims 1 to 7.
9. Application of the in-situ gel MOF mixed matrix membrane prepared according to any one of the methods of claims 1 to 7 in the selective separation of CO2 / N2 mixed gases.
Citation Information
Patent Citations
MOF-based mixed matrix membrane and preparation method thereof
CN113318605A
Mixed matrix membrane as well as preparation method and application thereof
CN116764462A
Mixed matrix polymeric membranes
US20150101986A1
Branched metal-organic framework nanoparticles in mixed-matrix membranes and associated methods
US20210129088A1
Cited By
Preparation method of metal organic framework gel mixed matrix membrane and application of metal organic framework gel mixed matrix membrane in CO2 / CH4 separation
CN119588187A
Composite MOF (Metal Organic Framework) membrane for gas separation and preparation method of composite MOF membrane
CN122032335A